Brain–Computer Interfaces on Track to Home: Results of the Evaluation at Disabled End-Users’ Homes and Lessons Learnt - Miralles, Felip; Vargiu, Eloisa; Rafael-Palou, Xavier; Solà, Marc; Dauwalder, Stefan; Guger, Christoph; Hintermüller, Christoph; Espinosa, Arnau; Lowish, Hannah; Martin, Suzanne; Armstrong, Elaine; Daly, Jean (Frontiers in ICT, 2015)
The BackHome system is a multi-functional BCI system, the final outcome of a User Centred Design approach, whose ambition is to move BCI systems from laboratories into the home of people in need for their independent home use. The paper presents the results of testing and evaluation of the BackHome system with end-users at their own homes. Results show moderate to good acceptance from end-users, caregivers and therapists; which reported promising usability levels, good user satisfaction and levels of control in the use of services and home support based on remote monitoring tools.